Survey on digital sovereignty and identity: from digitization to digitalization - Tan, Kheng Leong (2023)
Through digital transformation, lots of personal data are captured, but individuals often do not have ownership or control over them. This results in the emerging Web 3.0, where people demand data sovereignty. There are actually two conceptually related terms, data sovereignty and digital sovereignty. This paper first explains these two concepts in terms of their points of focus, guiding principles, laws and regulations requirements, and then analyses the requirements and technical challenges of their implementation. To understand the emerging trend shift in digital sovereignty towards individuals taking control of security and privacy preserving over their own digital assets, this paper conducts a systematic review and analysis on Self-Sovereign Identity (SSI), which is a user-centric decentralized model and autonomy for an individual to self-determine the access and use of one's identity and credentials. The review covers existing SSI solutions and points out that an efficient key management system, the scalability and interoperability of the solution, and a well-established standard are some of the challenges for SSI deployment. Finally, the paper concludes with open issues about digital identity, including dynamic attributes, persona, and attribute ownership, that challenge the current reference architecture of SSI as well as its implementation.